Improving of Personal Educational Content Using Big Data Approach for Mooc in Higher Education - Santur, Yunus; Karakose, Mehmet; Akin, Erhan (Ieee, 2016)
Today, web-based education technologies such as e-learning, distance learning, online course, virtual classrooms and interactive learning are commonly used outside the traditional education systems. Massive Open Online Courses, which were adopted with the evolution of these systems in 2008, have become the most popular education systems of today and access to a very large audiences with many modules such as video courses, documents, interactive learning activities and quizzes in themselves. In this study, a machine learning and big data based approach has been presented for the mentioned online education systems. With the proposed approach, it is aimed to develop course contents in online education, offer student-specific learning activities, perform an analysis according to criteria such as age, gender, occupation, education level and location, and to obtain decisions with strategic importance such as determining the course prerequisites to be developed by big data-based analysis.
15th International Conference on Information Technology Based Higher Education and Training (ITHET) -- SEP 08-10, 2016 -- Istanbul, TURKEY
Keywords: big data; massive open online course; mooc; higher education; machine learning; deep learning